Pengaruh Pertumbuhan dan Hasil Tanaman Caisim (Brassica juncea) Terhadap Pemberian Abu Dasar Batubara (Coal Bottom Ash) dan Bahan Organik - Rika Yayu Agustini (Universitas Bangka Belitung, 2018)
This study aims to determine the optimal dosage of bottom ash and organic matter which can increase the growth and yield of mustard plants. The study was carried out in the greenhouse of the Soil Physics Laboratory, Balai Penelitian Tanah, Laladon, Bogor from August 2015 to January 2016. The study used factorial complete randomized design (CRD). The first factor is the age of bottom ash (fresh, 4 months and 2 years). The second factor is the bottom ash dose with three levels, which are 0, 60 and 120 grams / pot (equivalent to 0, 40 and 80 tons / ha) and the third factor is the dose of organic matter with two levels, namely 0 and 15 grams / pot (equivalent to 0 and 10 tons / ha). The results showed that the addition of fresh bottom ash with a dose of 80 tons / ha and 10 tons / ha of organic matter significantly affected the plant height. While on the parameters of the number of leaves and fresh weight of mustard plant, the treatment that gives a significant effect is 10 tons / ha of organic matter. The best dose that can increase the growth and yield of mustard plants is fresh bottom ash with a dose of 80 tons / ha and 10 tons / ha of organic matter.